ANALISA KEMAMPUAN PREDIKSI ARUS KAS OPERASI MASA DEPAN - Dalenrs Dalenrs; Yuniarwati Yuniarwati (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to obtain empirical evidence on the influence of net profit, changes in payable, and changes in inventory toward future operating cash flow in manufacturing companies listed on the Indonesia Stock Exchange in 2016 – 2018. The study used 74 samples from manufacturing companies selected by purposive sampling method. The data used is secondary data in the form of financial statements. Data processing in this study using E-views program version 10.0. The results of this study showed those net profit and Changes in payable have a positive effect on future operating cash flow, and changes in inventory have a negative effect on future operating cash flow. Further research had expected to add independent variables, extend the research period, and use sectors other than manufacturing companies.